Managing PeopleSoft on the Oracle cloud : best practices with PeopleSoft Cloud Manager - Engelsrud, Aaron (Apress, 2019)
Transition from hosting your PeopleSoft applications in a traditional, on-premises data center to hosting those same applications in the Oracle Cloud infrastructure. This functional and technical book helps you install and support PeopleSoft Cloud Manager and makes the case for moving applications to the Oracle Cloud technology stack. You will learn about the use and cost of PeopleSoft instances in the cloud and how to configure your PeopleSoft environments to take advantage of the Oracle Cloud platform. Managing PeopleSoft on the Oracle Cloud is a resource for the functional analyst or IT manager tasked with moving PeopleSoft to the Oracle Cloud, as well as for the PeopleSoft system administrator or developer tasked with keeping a PeopleSoft installation running smoothly. Multiple cloud use cases illustrate PeopleSoft system configuration best practices, spell out specific requirements for running PeopleSoft Cloud Manager on the Oracle Cloud, and outline tips and tricks for running PeopleSoft instances in the cloud. What You'll Learn: Install and configure PeopleSoft Cloud Manager Subscribe to maintenance releases and updates Create new topologies and build new environment templates Instantiate and manage PeopleSoft instances using Cloud Manager Transition PeopleSoft from on site to in the cloud.